Locus heterogeneity in autosomal dominant congenital external ophthalmoplegia (CFEOM). Issue 12 (December 1998) - Black, G C; Perveen, R; Hatchwell, E; Reck, A; Clayton-Smith, J
Abstract : Congenital external ophthalmoplegia (CFEOM) is an uncommon autosomal dominant condition that has previously been mapped to the pericentromeric region of chromosome 12 in seven families with no evidence of locus heterogeneity. We report three families with typical CFEOM. One family does not map to this region of chromosome 12 or to other chromosomal locations implicated in disorders of lid or ocular movement. Recombinants in two CFEOM families potentially help to reduce the size of the candidate region on chromosome 12.